Therapeutic Effect and Mechanism of Bushen-Jianpi-Jiedu Decoction Combined with Chemotherapeutic Drugs on Postoperative Colorectal Cancer - Yang, Meng-Die (Front Pharmacol, 2021)
There is a lack of effective therapeutic drugs in patients with postoperative colorectal cancer (PCRC). This study aimed to investigate the therapeutic effect and mechanisms of Bushen-Jianpi-Jiedu decoction (BSJPJDD) combined with chemotherapeutic drugs (oxaliplatin) on PCRC with liver and kidney yin deficiency and spleen deficiency syndrome (LKYD-SDS) through the therapeutic evaluation of clinical therapy and the integrative analysis of network pharmacology, RNA-seq and label-free data, and experiment verification in vitro. In clinical therapy, the median progression-free survival (PFS) and Karnofsky performance score (KPS) were increased in PCRC patients by the aqueous extract of BSJPJDD combined with oxaliplatin treatment for three months, compared to oxaliplatin alone (p < 0.05). The integrative analysis showed that 559 differentially expressed genes (DEGs) and 11 differentially expressed proteins (DEPs) were regulated by BSJPJDD, among which seven bioactive compounds through 39 potential targets were involved in the regulation of multiple signaling pathways including MAPK, PI3K-Akt, and HIF-1, etc. In the experimental verification, an ELISA assay showed that plasma ZEB2, CAT, and KRT78 were decreased, and IL-1Α, CD5L, FBLN5, EGF, and KRT78 were increased in comparison to the above (p < 0.05). Furthermore, the SW620 cell viability was inhibited and the expressions of MAPK and the p-ERK/ERK ratio were significantly downregulated by the aqueous extract of BSJPJDD combined with oxaliplatin treatment, compared with oxaliplatin treatment alone (p < 0.05). These data suggested that BSJPJDD combined with oxaliplatin prolongs the survival and improves Karnofsky performance status of PCRC patients with LKYD-SDS, and may be associated with the regulation of multiple signaling pathways.